Valoración de la producción científica sobre el pensamiento crítico en los procesos cognitivos de la formación : una revisión desde la teoría de redes (2018)
ABSTRACT: A measurement of the theoretical and methodological knowledge of Critical Thinking (CT) production is presented in education under the Network Analysis methodology, identifying lines and authors that have the most impact on existing production and which are taken up in other scientific production to resize and to create new definitions, representing the main current in the field. This condition makes these lines and authors of mandatory review to conduct research on CT. Therefore, this work provides a structure of knowledge that makes it possible to establish current and future research and discussions on the subject, as well as a methodological path for the construction of the state of the art based on scientometric measurements.